Pain knowledge and attitudes of final year medical students at the University of Cape Town: a cross-sectional survey - Mashanda-Tafaune, Blessing (Department of Anaesthesia and Perioperative Medicine, 2021)
Background: Pain is the most common presenting complaint in patients visiting a healthcare facility. Healthcare professionals need adequate knowledge of pain to be able to manage it effectively. Aim: To determine the Pain Knowledge and Attitudes of the 2018 final year medical students at the University of Cape Town (UCT). Setting: The study was conducted by the Department of Anaesthesia and Perioperative Medicine in the Faculty of Health Sciences, University of Cape Town, South Africa with final year medical students Methods: Unruh's Modified Pain Knowledge and Attitudes (MPKA) questionnaire was utilized to collect data in a cross-sectional survey using an internet-based electronic format. Results: A total of 104 students out of 232 students in the class (44.8%) participated in the study. The total median score on the MPKA questionnaire was 46 (IQR 44- 50.5) out of 57, or 80.7%(IQR 77.2-88.6%).The participants performed worst in the section on the pharmacological management of pain with median scores of 6 (IQR 4- 8) (55%) correct out of 11 questions. Conclusion: Pain knowledge, especially with regards to the pharmacological aspects of pain management, has some important deficiencies in these final year medical students. It appears that the undergraduate curriculum and teaching thereof would benefit from a review of the pain curriculum.